(untitled) (Revista Sistemas de Producción Agroecológicos, 2010)
The objective of this project was to evaluate the leucaena (Leucahena lecucephala) as a supplement in sheep grazing. Using 12 males African (Sudanese), average weight of 14.45 kg, with a base diet of braquiaria (B. decumbens), the sheeps were randomly distributed entirely to the three replications and four treatments: T1 (control): braquiaria, T2: braquiaria plus 1% of live animal weight of dry matter of leucaena (DML), T3 braquiaria, 1.5 % of DML and T4: braquiaria plus 2.0% of DML. The sheep remained in bands divided with electric fence and were rotated daily. The sheeps were weigthed every seven days during the two months. In four sheeps, with a weight of 15 kg were housed in metabolic cages, were given the same treatments to assess the digestibility in vivo. At the braquiaria and leucaena were analyzed for estimate dry matter, protein, fat, Crude fiber, and ash, neutral detergent fiber (NDF) and acid detergent fiber (ADF) The collected excreta were also analized to determinate the same nutrients of the forages. With this information were calculated digestibility coefficients (COD) and total digestible nutrients (TDN). The protein content in leucaena is 19.3%, while that of grass is 8.5% 2.29 times that of the legume compared with grass. The digestibility of DM and protein were higher (P>0.05) in T3 and T4, compared with the other two treatments. The total weight gains and daily were higher (P>0.05) for T3 and T2 followed by T4 that are higher (P> 0.05) at T1. The DM intakes were higher (P>0.05) T1 and T4 and T3 compared with T2. The best feed conversion (P>0.05) on DM intake was T3 followed by T2, T4 and T1. Undoubtedly, using leucaena fed to ruminants as a supplement to a grass is advantageous because its nutrient content allows it to offer a balanced diet without detriment to its productive indices, especially in areas where forages are of low quality.